THE IMPACT OF PRENATAL EDUCATION THROUGH STIMULATING QURAN’S RECITATION ON CHILD’S GROWTH - Suciati Suciati (P3M STAIN Kudus, 2015)
A child is the greatest gift from the God after marriage. Giving the best to him is a must. Parents are always selective in giving education. That education can be started since they are still in the womb. It is named prenatal education. Although a fetus or baby is still in the womb, his hearing and understanding develop well because of stimulus from outside. Giving education is not just for intelectual, but also for mental and spiritual. A mother should know and give the best thing for her baby. Quran is the basic thing for moslems’ life. A pregnant woman who listens, reads, or recites Quran feels comfort. Her baby will feel the same because mother’s condition influences baby’s condition. Various researchers showed that pregnant women who read, recite or listen to the Quran can give good impact to the fetus or baby in the womb. It does not just influence the baby’s Intelligence Quotient (IQ) and Emotional Quotient (EQ), but it also gives Spiritual Quotient (SQ) to the baby.